2019
DOI: 10.1111/jcpp.13115
|View full text |Cite
|
Sign up to set email alerts
|

Oral contraceptive use in adolescence predicts lasting vulnerability to depression in adulthood

Abstract: Background Previous evidence suggests that use of oral contraceptives (OCs), especially during adolescence, may increase women's vulnerability to depression in the short term. Here, we investigate whether women who had first used OC in adolescence show an increased prevalence of depression in the long term. Methods We examined 1,236 women in the United States National Health and Nutrition Examination Survey for whom information on depression and age at first OC use was publicly available. We compared women who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
62
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 42 publications
5
62
0
2
Order By: Relevance
“…Given several athletes in this cohort have previously used an HC, and the second most common reason for discontinuation was that they wanted to take a "natural" approach, understanding the changing attitudes toward the use of HC may be an important consideration. There is a growing body of literature to suggest negative effects such as depression (Anderl et al, 2020), poorer bone mineral density (Allaway et al, 2020), and greater oxidative stress (Cauci et al, 2016) with HC use. However, these effects may be specific to the HC type, with OC the main focus of research looking at these such side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given several athletes in this cohort have previously used an HC, and the second most common reason for discontinuation was that they wanted to take a "natural" approach, understanding the changing attitudes toward the use of HC may be an important consideration. There is a growing body of literature to suggest negative effects such as depression (Anderl et al, 2020), poorer bone mineral density (Allaway et al, 2020), and greater oxidative stress (Cauci et al, 2016) with HC use. However, these effects may be specific to the HC type, with OC the main focus of research looking at these such side effects.…”
Section: Discussionmentioning
confidence: 99%
“…In recreational to elite level Australian athletes, the use of HC use is slightly lower at ∼40% (Armour et al, 2020), likely due to the inclusion of recreational level participants. Despite the advantages of using HC to control their menstrual cycle and potentially reduce menstrual-related symptoms, evidence suggests potential negative outcomes associated with HC use such as a higher risk for depression (Anderl et al, 2020), lower bone mineral density (Allaway et al, 2020), and greater oxidative stress (Cauci et al, 2016), particularly with OC methods. Understanding the reasons why athletes use HC is important to inform athletes' decision to start, stop, or switch between different HC options.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, these studies point out that adolescents were at higher risk relative to women older than 20 years, which has since been replicated in an independent prospective cohort study (9). Further, another study suggests that first time use of OCs in adolescence compared to in adulthood is associated with longer lasting vulnerability to MDD through adulthood (10). The literature, however, shows conflicting results as smaller studies have reported positive or no mood effect of OC use (11).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the associations between cortisol concentrations and OC intake, the use of OC has been associated with a higher risk of depression and higher use of antidepressant medication, especially in adolescents [ 12 , 61 , 62 ]. A history of psychiatric symptoms strengthened the effects [ 35 ].…”
Section: Discussionmentioning
confidence: 77%